Saving the international justice regime : beyond backlash against international courts - Hillebrecht, Courtney (Cambridge : Cambridge University Press, 2021)
While resistance to international courts is not new, what is new, or at least newly conceptualized, is the politics of backlash against these institutions. Saving the International Justice Regime: Beyond Backlash against International Courts is at the forefront of this new conceptualization of backlash politics. It brings together theories, concepts and methods from the fields of international law, international relations, human rights and political science and case studies from around the globe to pose - and answer - three questions related to backlash against international courts: What is backlash and what forms does it take? Why do states and elites engage in backlash against international human rights and criminal courts? What can stakeholders and supporters of international justice do to meet these contemporary challenges?
Progress and pushback in the judicialization of human rights -- Backlash in theoretical context -- The politics of withdrawal -- Replacing the international justice regime -- Bureaucrats, budgets and backlash : death by a thousand paper cuts -- Doctrinal challenges : diluting the domestic impacts of international adjudication -- How to save the international justice regime.
Title from publisher's bibliographic system (viewed on 21 Sep 2021).
Keywords: International Criminal Court; International criminal courts -- Political aspects